Mediating effects of service quality management and empowerment on the relationship between leaders' behavior and job satisfaction amongst University lecturers in Pakistan - Jabbar, Muhammad Naveed (2020)
In modem era higher education plays a vital role for the socio-economic growth of the countries. Similarly, the ultimate goal of higher education in Pakistan is to produce experienced and skillful human capital in order to make county a developed nation. This goal can be achieved through effective teaching conducted by the lecturers. However, the teaching conducted by the university lecturers is less effective due to the lack of job satisfaction. Nevertheless, this idea is insufficiently deliberated at the university level in Pakistan. In this context, the effective behavior of leaders and lecturers' job satisfaction crucially drive the excellence of higher education institutions. Hence, the leaders need to adopt supportive behavior for the enhacement of job satisfaction. The effectiveness of leaders' behavior on job satisfaction was explained through structural model which also highlighted the role of service quality management and empowerment as mediator. A quantitative cross-sectional research design was used for this study involving 461 lecturers who were sampled by using a stratified random sampling technique. A survey method was used to collect the data through standardised questionnaires. SPSS ver. 25 and Smart PLS-SEM-3 were employed to analyse the data. The results show that lecturers' were moderately satisfied with their job. In addition, service quality management and empowerment have a positive and significant mediating effect on the relationship between leader behavior and job satisfaction of university lecturers in Pakistan. In conclusion, the findings proved that leaders' behavior, service quality management and empowerment enhance the job satisfaction. This study is beneficial for the leaders in order to adopt effective behavior for the improvement of lecturers' job satisfaction. Moreover, it provides the meaningful significant contribution for the sustainable development of higher education institutions by adopting new strategies and techniques through valuable human resources.